The effectiveness of pay-for-performance contracts with non-governmental organizations in Afghanistan - results of a controlled interrupted time series analysis - Diwa Samad; Bashir Hamid; Ghulam Dastagir Sayed; Yueming Liu; Wu Zeng; Alexander K. Rowe; Benjamin Loevinsohn (BMC, 2023)
Abstract Background In many contexts, including fragile settings like Afghanistan, the coverage of basic health services is low. To address these challenges there has been considerable interest in working with NGOs and examining the effect of financial incentives on service providers. The Government of Afghanistan has used contracting with NGOs for more than 15 years and in 2019 introduced pay-for-performance (P4P) into the contracts. This study examines the impact of P4P on health service delivery in Afghanistan. Methods We conducted an interrupted time series (ITS) analysis with a non-randomized comparison group that employed segmented regression models and used independently verified health management information system (HMIS) data from 2015 to 2021. We compared 31 provinces with P4P contracts to 3 provinces where the Ministry of Public Health (MOPH) continued to deliver services without P4P. We used data from annual health facility surveys to assess the quality of care. Findings Independent verification of the HMIS data found that consistency and accuracy was greater than 90% in the contracted provinces. The introduction of P4P increased the 10 P4P-compensated service delivery outcomes by a median of 22.1 percentage points (range 10.2 to 43.8) for the two-arm analysis and 19.9 percentage points (range: - 8.3 to 56.1) for the one-arm analysis. There was a small decrease in quality of care initially, but it was short-lived. We found few other unintended consequences. Interpretation P4P contracts with NGOs led to a substantial improvement in service delivery at lower cost despite a very difficult security situation. The promising results from this large-scale experience warrant more extensive application of P4P contracts in other fragile settings or wherever coverage remains low.